Potensi Cendawan Endofit pada Tanaman Binahong (Anredera cordifolia (Ten.) Steenis) untuk Mengendalikan Botryodiplodia theobromae Pat. Penyebab Mati Pucuk pada Bibit Jabon (Anthocephalus cadamba (Roxb.) Miq) - Yunik Istikorini (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2019)
Endophytic fungi provides potential advantages as biocontrol agents in the plant. Binahong (Anredera cordifolia) is a medicinal plant which can potentially overcome many kinds of diseases. The dieback disease is caused by Botryodiplodia theobromae Pat. that may lead the death of the host. The objective of this research was to analyze the potency of endophytic fungi from binahong leaves to control the fungus B. theobromae as causal agent of dieback disease on jabon (Anthocepalus cadamba). The isolates of endophytic fungi from binahong used were bnh1.1, bnh1.2, bnh1.3, bnh4.2, bnh4.5, bnh3.3 and bnh3.4. The antifungal effect of endophytic fungi againts colony growth of virulent B. theobromae were tested in vitro. The results showed that all endophytic fungus (7 isolates) inhibited the colony development of B. theobromae ranging from 28.52%-52.22%. Treatment with endophytic fungi bnh4.5 and bnh4.2 had protected jabon from virulent B. theobromae. It has been expressed by the delay of the incubation period and the decreasing of disease severity (respectively 33.34% and 40.84%. Key words: Anredera cordifolia, Botryodiplodia theobromae, disease incidence, endophytic fungi